Direct numerical simulation of flow and heat transfer in a simplified pressurized thermal shock scenario. (June 2019) - Shams, A.; De Santis, D.; Rosa, D.; Kwiatkowski, T.; Komen, E.J.M.
Highlights: DNS is carried out to analyse the flow and thermal fields in a simplified Pressurized Thermal Shock scenario. The configuration consists of a square duct that intersects perpendicularly with a rectangular domain. The thermal field is treated as a passive scalar with the use to iso-flux and isothermal boundary conditions. Abstract: Direct numerical simulation (DNS) is carried out using a high order spectral element method in order to analyse the flow and thermal fields in a Pressurized Thermal Shock (PTS) scenario. The adopted configuration is representative of a simplified reactor pressure vessel. It consists of a square duct that intersects perpendicularly with a rectangular vessel (downcomer). Cold water is injected from the square duct. It impinges against the wall of the downcomer that contains water at higher temperature, and a mixing between the cold and hot water occurs in the downcomer. The fluid properties are assumed to be constant; hence the temperature is treated as a passive scalar. A secondary flow inlet in the upper part of the downcomer is used to mimic the effect of density driven flow. The friction Reynolds number in the duct equals to 180, and a unitary Prandtl number of the fluid is used. The thermal field is solved with two types of boundary conditions, i.e., iso-thermal and adiabatic conditions, which encompass the two extreme scenarios of a conjugate heat transfer problem. A careful meshing strategy is adopted and the mesh resolution is verified a posteriori in order to meet DNS quality. The mean flow and turbulent statistics are analysed first, and a particular attention is devoted to the analysis of the vortical structures at the edges of the duct flow. The instantaneous flow field is then analysed in order to study the turbulent structure and the vorticity field within the impingement region. The mean temperature and the turbulent statistics of the thermal fields are subsequently analysed for both thermal boundary conditions. The case with iso-thermal boundary condition corresponds to the initial phase of the thermal mixing during a PTS scenario. It is characterized by the presence of cold fluid near the impinging wall and pockets of fluid at higher temperature near the exit of the duct. Regions with large temperature fluctuations are observed near the edges of the duct and at the interface between the deflected impinging fluid and the descending fluid in the downcomer. The case with adiabatic boundary condition corresponds to the later stage of the thermal mixing during a PTS scenario in which a thermal equilibrium is reached. For this case, a region with lower temperature is observed in the downcomer within the impinging jet region and in the region below, whereas the fluid at higher temperature remains confined in the remaining part of the downcomer.